(untitled) (Pursuits: A Journal of English Studies, 2022)
Coelho’s Hippie is based on the time in which Coelho is living the way of a hippie. Spiritual seekers make their way to India and even Nepal in the sixties in search of enlightenment. In the 1960s, the groups of unconventional appearance are associated with a subculture and reject conventional values. The paper tries to meet its objective by explaining how the protagonist cultivates his journey and achieves the spiritual awakening in the end of his journey. This paper explores issues of Quest of Spiritual Knowledge in Paulo Coelho’s Hippie through the lens of popular culture because in the today’s world the text is connected to its cultural archetype. It interprets the issue of the hero quest and spiritual education in Coelho’s text and then its connection with popular culture. Coelho’s Hippie relates to how Paulo as well as the other young boys and girls challenge western and non-western concept of culture, and they leave their homes to experiment the world on their own. These youths appear to create and organize the hippie culture, live in separate commune and travel far and wide in quest of peace, freedom and love as protest. To interpret the text, I apply the readings and concepts of Joseph Campbell, John Storey, Ray Brown and Marshall Fishwick as a theoretical framework. The paper argues that although the hippie culture progresses as the counterculture of the 1960s youth movement, the protagonist’s quest of spiritual awakening is an issue of the study.